Analisis “Bab IV Satu Titik” Buku Siswa Kelas 4 SD Berdasarkan Kelayakan Buku BSNP Berbantuan EYD Edisi V - Darwoto, Devianti Revalia Wijaya; Purwati, Panca Dewi; Putra, Hafied Ardy; Zaharoh, Sofiatul; Najwatin, Binta Safira; Saputri, Tia Aprilliana (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
The purpose of this study is to analyze the feasibility of content, language, presentation, and graphography in Chapter 6 "One Point" in the Indonesian textbook for grade IV elementary school students, based on the criteria set by the National Education Standards Agency (BSNP) and guided by the Improved Indonesian Spelling (EYD) Edition V. The approach used in this study is a qualitative descriptive approach with a content analysis method. The data source comes from the chapter "One Point" in the Indonesian book published in 2021. The analysis focused on four aspects of textbook feasibility: content feasibility, language feasibility, presentation feasibility, and graphic feasibility, with reference to the BSNP assessment indicators and linguistic rules in EYD Edition V. The results of the research obtained showed that the book generally met the feasibility standards in terms of content suitability with learning objectives, material up-to-date, and linguistic accuracy. However, some errors were found in punctuation, word selection, and clarity of sentence structure that needed to be corrected. The graphic and presentation aspects are considered appropriate and attractive for elementary school students. This analysis emphasizes the importance of regular textbook evaluation to ensure that teaching materials remain accurate, effective, and relevant. Keywords: Textbook analysis, textbook feasibility, BSNP standards, Indonesian, EYD Edition V